Indices determining effective teaching of physical education in secondary school teachers in Ilorin West Local Government Area - Oluwatoyin, Ibraheem Musa; Sofyan, Davi; Abdulrazaq, Ambali (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
Many factors cause students' physical education learning outcomes to be not so encouraging, ranging from learning infrastructure, teacher competence, learning environment, learning curriculum. The purpose of this study was to investigate the index of determining the effective teaching of physical education in secondary schools in West Ilorin Local Government Area, Kwara State, Nigeria. Descriptive research design of survey type is used in this research. The population for this study consisted of sixty-five (65) physical education teachers in both public and private secondary schools. Four five (45) public secondary schools and twenty (20) private secondary schools were deliberately selected for this study. The questionnaire was well structured and designed by the researcher as the instrument used for data collection. The instrument was validated and the reliability of the instrument was confirmed through the split-half method. This instrument was given to 20 respondents from the East Ilorin Regional Government, Kwara State. All items on even numbers are scored separately, as well as scores on odd items. Both scores were analyzed using Cronbach's alpha, which yielded 0.62r. Sixty-five (65) questionnaire forms were taken and analyzed using PPMC and Multiple Linear Regression at an alpha level of 0.05. Based on the research findings, it is concluded that the Index (teaching materials, teaching strategies and school factors) determines the effectiveness of teaching physical education in junior high schools in the Ilorin Local Government Area of ​​Kwara State, Nigeria. The researcher recommends that this type of research should be conducted in other Local Government Areas in Kwara State to investigate the index that determines effective physical education teaching.